A passivation method for perovskite film
By using benzamidine hydrochloride solution on the surface of perovskite solar cell films to form a low-dimensional passivation layer, the problem of hollow defects in the film is solved, the stability and conversion efficiency of the film are significantly improved, and efficient passivation is achieved Effect.
Patent Information
- Application Number
- CN202410433357.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-11
AI Technical Summary
There are a large number of vacancy defects in the existing perovskite solar cell films, resulting in non-radiative recombination, reducing conversion efficiency and affecting performance stability.
A low-dimensional passivation layer was formed on the surface of the perovskite film by slit coating using benzamidine hydrochloride solution to eliminate vacancy defects and passivation of the perovskite film was achieved.
It effectively improves the stability and photoelectric performance of perovskite films, improves the conversion efficiency of solar cell devices, and achieves more than 18% energy conversion efficiency in large-area modules.
Smart Images

Figure CN118139496B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cell modules, and in particular relates to a passivation method for a perovskite film. Background Art
[0002] Solar energy is pollution-free and is considered one of the most valuable emerging energy sources. Making full use of solar energy is of great significance to reducing greenhouse and polluting gas emissions and achieving sustainable development.
[0003] Solar cells use the photovoltaic effect to convert solar energy into electrical energy. After decades of development, the first generation of silicon-based cells, the second generation of film cells, and finally the development of perovskite solar cells (PSCs) have been completed. Perovskite films have adjustable band gaps, good light absorption performance, and long carrier diffusion distances (micrometer level). They can be printed by solution method, which is more advantageous than traditional photovoltaic materials.
[0004] Organometallic halide perovskite (ABX 3 ) film is a polycrystalline film, which is composed of closely arranged grains. There are usually a large number of defects at the interface and grain boundary, which greatly affects the overall performance of the film. Due to the influence of the film preparation process and the precursor solution formula, vacancy defects in the film, especially the cation vacancy defects at the A position and the halide ion vacancy defects at the X position are the most common. The presence of these defects will lead to serious non-radiative recombination, reducing the solar cell conversion efficiency (PCE); secondly, the presence of defects will greatly accelerate the aging speed of the film, seriously affecting the performance stability of the film. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a passivation method for perovskite film by using benzamidine hydrochloride (C 7 H 9 C1N 2 ) Eliminating vacancy defects in perovskite films and forming low-dimensional perovskites to passivate the perovskite films can effectively improve the stability of large-area perovskite films, thereby improving the conversion efficiency of solar cell devices.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] A method for passivating a perovskite film is provided, comprising the following steps:
[0008] 1) Preparation of FAPbI with surface-rich lead iodide grains 3 Perovskite film: FAPbI 3The perovskite precursor solution is coated on a conductive substrate with an electron transport layer, and then the conductive substrate is annealed to obtain FAPbI with surface-rich lead iodide grains on the surface of the conductive substrate. 3 Perovskite thin films;
[0009] 2) Preparation of passivation layer: Apply the benzamidine hydrochloride solution to the FAPbI obtained in step 1) by slit coating method. 3 The surface of the perovskite film is then annealed to form benzamidine hydrochloride and FAPbI 3 Lead iodide on the surface of the perovskite film reacts to form a low-dimensional passivation layer, thereby passivating the perovskite film.
[0010] According to the above scheme, the conductive substrate in step 1) is an FTO or ITO substrate after etching and cleaning.
[0011] According to the above scheme, the electron transport layer in step 1) is one of tin oxide film, titanium oxide film and zinc oxide film.
[0012] According to the above scheme, step 1) the FAPbI 3 The thickness of the perovskite film is 600-800 nm, and the preparation method thereof is as follows: formamidine hydroiodide (FAI), PbI 2 , methylamine hydrochloride (MACl) powder and lead chloride (PbCl 2 ) was dissolved in a mixed solvent to obtain FAPbI 3 Perovskite precursor solution, resulting FAPbI 3 The perovskite precursor solution is printed onto the surface of a conductive substrate with an electron transport layer by a slit coating method. The slit width between the printing head and the conductive substrate is 100-150 μm, the moving speed of the printing head is 4-7 mm / s, the liquid output rate is 0.6-1.5 mL / min, and the air pressure of the air knife is 0.3-0.6 MPa. Then, the perovskite precursor solution is annealed at 120-150 ° C for 30-60 min to obtain FAPbI on the surface of the conductive substrate. 3 Perovskite thin films.
[0013] According to the above scheme, the concentration of FAI in the perovskite precursor solution is 1.0-1.2M (mol / L), PbI 2 The concentration of FAI is 0.2 M higher than that of FAI. The excess lead iodide is used to form PbI on the surface of the perovskite film. 2 grains, MACl concentration is 0.1~0.3M, PbCl 2 The concentration is 0.01~0.04M.
[0014] According to the above scheme, the mixed solvent is obtained by mixing ethylene glycol methyl ether (2-ME) and dimethyl sulfoxide (DMSO) in a volume ratio of 9:1.
[0015] According to the above scheme, the concentration of the benzamidine hydrochloride solution in step 2) is 1.0-6.0 mg / mL, which is obtained by dissolving benzamidine hydrochloride in a mixed solvent of isopropanol (IPA), ethyl acetate (EA) and N,N'-dimethylformamide (DMF), wherein the volume ratio of isopropanol to ethyl acetate is 9:1, and the amount of N,N'-dimethylformamide added per milliliter of the mixed solvent is 4-8 μL.
[0016] According to the above scheme, the process conditions of the slit coating method in step 2) are: the gap width between the printing head and the conductive substrate is 80-120 μm, the moving speed of the printing head is 5-10 mm / s, and the liquid discharge rate is 0.3-0.6 mL / min.
[0017] According to the above scheme, the annealing process conditions in step 2) are: annealing temperature is 100-120° C., and annealing time is 10-20 min.
[0018] According to the above scheme, the low-dimensional passivation layer in step 2) is a two-dimensional perovskite.
[0019] The present invention also includes a perovskite film prepared according to the above passivation method.
[0020] Furthermore, the present invention also includes a perovskite solar cell prepared according to the above-mentioned perovskite film, and its specific preparation method is: depositing a hole transport layer on the surface of the perovskite film, and then depositing an electrode (such as a gold electrode) on the surface of the hole transport layer to obtain a perovskite solar cell.
[0021] Furthermore, the present invention also includes a large-area perovskite solar cell module prepared according to the above-mentioned perovskite film, and its specific preparation method is: depositing a hole transport layer on the surface of the perovskite film, and then dividing it into multiple areas by laser scribing, and then depositing electrodes on the surface of the hole transport layer, and laser scribing again, so as to obtain a large-area perovskite solar cell module.
[0022] According to the above scheme, the thickness of the hole transport layer is 200-300 nm.
[0023] According to the above scheme, the thickness of the gold electrode is 80-100 nm.
[0024] The present invention develops a benzamidine hydrochloride solution for passivating large-area perovskite films, that is, first preparing FAPbI with a surface rich in lead iodide grains. 3The perovskite film is then prepared by dissolving benzamidine hydrochloride in a mixed solvent of IPA, EA and DMF and printing the resulting solution onto the surface of the perovskite film by slit coating. The addition of EA and a trace amount of DMF in the mixed solvent can make the benzamidine hydrochloride cover more uniformly and react more fully with the lead iodide on the surface of the film to form a low-dimensional passivation layer, thus achieving the three-dimensional FAPbI 3 Passivation of perovskite film. At the same time, the formation of a low-dimensional passivation layer can achieve better energy level matching, facilitate carrier transport, and achieve performance improvement.
[0025] The beneficial effects of the present invention are as follows: the passivation method of the present invention can effectively eliminate the defects in the perovskite film, and in the three-dimensional FAPbI 3 The low-dimensional perovskite formed on the surface of the perovskite film can passivate the original film well, so that the stability and photoelectric performance of the perovskite film are significantly improved. The benzamidine hydrochloride solution of the present invention can be printed by a slit coating method, so it is suitable for preparing large-area perovskite solar cell modules, achieving 12×12cm 2 The energy conversion efficiency of perovskite solar cell modules is over 18%. After 600 hours of maximum power point tracking, the treated battery devices can still maintain an energy conversion efficiency of over 80%, which has huge potential for commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the cross-sectional structure of a large-area perovskite solar cell module prepared in Example 1;
[0027] Figure 2 The photos are of the perovskite film and the large-area perovskite solar cell module prepared in Example 1;
[0028] Figure 3 The scanning electron microscope images of the surface of the perovskite film before and after passivation of the perovskite film of Example 1 and Comparative Example 1 and Comparative Example 3 after passivation treatment;
[0029] Figure 4 X-ray diffraction diagrams of the perovskite film before and after passivation of Example 1 and the perovskite film after passivation treatment of Comparative Example 1 and Comparative Example 3;
[0030] Figure 5 X-ray diffraction diagram of the perovskite film before and after passivation treatment in comparative example 2;
[0031] Figure 6 The ultraviolet photoelectron spectrum and energy band structure diagram of the perovskite film before and after passivation treatment in Example 1;
[0032] Figure 7 JV curves of large-area perovskite solar cell modules prepared in Example 1 and Comparative Example 1;
[0033] Figure 8 V of the perovskite solar cells prepared in Example 1, Comparative Example 1 and Comparative Example 3 OC As the light intensity changes, the slope after linear fitting shows that the defect leads to non-radiative recombination;
[0034] Fig. 9 This is a long-term working stability test diagram of the large-area perovskite solar cell modules prepared in Example 1, Comparative Example 1 and Comparative Example 3. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.
[0036] Example 1
[0037] A method for passivating and encapsulating a large-area perovskite film and preparing a large-area perovskite solar cell module comprises the following steps:
[0038] 1) A FTO substrate (12 cm × 12 cm) was scribed using a laser etching device (P1), and then the FTO substrate was cleaned and ultrasonically cleaned in deionized water, ethanol, and isopropanol for 15 min, dried with nitrogen, and treated with ultraviolet ozone (UVO) for 15 min. Then, a tin oxide film was deposited on the cleaned FTO surface by chemical bath deposition as an electron transport layer with a thickness of about 5-10 nm;
[0039] 2) Formamidine hydroiodide (FAI), PbI 2 , methylamine hydrochloride (MACl) powder and lead chloride (PbCl 2 ) was dissolved in a mixed solvent to obtain a perovskite precursor solution, in which the concentration of FAI was 1.2 M, PbI 2 The concentration is 1.4M, the concentration of MACl is 0.2M, and the concentration of PbCl 2 The concentration of is 0.02M, and the mixed solvent is obtained by mixing ethylene glycol methyl ether and dimethyl sulfoxide in a volume ratio of 9:1. The obtained perovskite precursor solution is printed on the surface of the FTO substrate with an electron transport layer by a slit coating method to prepare a perovskite film. The specific parameters are: the gap width between the FTO substrate and the liquid outlet head is 120μm, the moving speed of the liquid outlet head is 5mm / s, the liquid outlet rate is 1.0mL / min, and the air pressure of the air knife is 0.5Mpa. After the coating is completed, annealing is performed at 120℃ for 30min to obtain a black and bright perovskite film with a thickness of 600-700nm, and its surface is rich in lead iodide grains;
[0040] 3) dissolving benzamidine hydrochloride in a mixed solvent of isopropyl alcohol (IPA), ethyl acetate (EA) and N,N'-dimethylformamide (DMF) to obtain a benzamidine hydrochloride solution, wherein the concentration of benzamidine hydrochloride is 2.0 mg / mL, the volume ratio of IPA and EA in the mixed solvent is 9:1, and the addition ratio of DMF is 4 μL DMF per milliliter of the mixed solvent. The obtained benzamidine hydrochloride solution is used to prepare a passivation layer on the surface of the perovskite film by a slit coating method. The specific parameters are: the gap width between the FTO substrate and the liquid outlet head is 100 μm, the moving speed of the liquid outlet head is 7 mm / s, and the liquid outlet rate is 0.4 mL / min. After the coating is completed, the substrate is annealed at 100° C. for 10 min to obtain a passivation layer (a low-dimensional perovskite film with a thickness of about 1-5 nm) on the surface of the perovskite film;
[0041] 4) Preparation of a hole transport layer on the surface of the passivation layer: 914.0 mg of Spiro-OMeTAD, 356.0 μL of 4-tert-butylpyridine (t-BP), 110.0 μL of lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI, dissolved in acetonitrile at a concentration of 0.25 M) and 210 μL of cobalt(III)bis(trifluoromethanesulfonyl)imide salt (FK209Co(III)TFSI, dissolved in acetonitrile at a concentration of 1.80 M) were dissolved in 2 A hole transport layer solution is obtained from a mixed solution of 0 mL of chlorobenzene and ethyl acetate (volume ratio of 1:1), and the obtained hole transport layer solution is printed onto the surface of the perovskite film by a slit coating method to obtain a hole transport layer with a thickness of 200-300 nm. Subsequently, laser scribing is performed on the surface of the hole transport layer (P2), and then a gold electrode with a thickness of 80 nm is deposited on the surface of the hole transport layer by thermal evaporation, and laser scribing is performed again (P3) to obtain a large-area perovskite solar cell module.
[0042] The schematic diagram of the cross-sectional structure of the large-area perovskite solar cell module prepared in this embodiment is as follows Figure 1 As shown, the glass substrate and the conductive substrate in the figure are FTO substrates.
[0043] Figure 2 The middle left is a photo of the perovskite film obtained in step 2) of this embodiment, and the right is a photo of the large-area perovskite solar cell module obtained in step 4). Figure 3 A is a SEM image of the perovskite film obtained in step 2) of this embodiment, and B is a SEM image of the perovskite film with a passivation layer on the surface obtained in step 3). It can be seen that the surface of the perovskite film obtained in step 2) is rich in lead iodide grains, and after the passivation treatment in step 3), the lead iodide grains on the surface of the perovskite film disappear, and the non-radiative recombination caused by defects is greatly reduced.
[0044] Figure 4The blank group in the middle is the XRD pattern of the perovskite film obtained in step 2) of this embodiment. At this time, the diffraction peak of lead iodide appears in the perovskite film. Example 1 is the XRD pattern of the perovskite film with a passivation layer on the surface obtained in step 3) of this embodiment. At this time, the perovskite film after passivation treatment shows the diffraction peak of low-dimensional perovskite.
[0045] Figure 6 A is the ultraviolet photoelectron energy spectrum of the perovskite film obtained in step 2) of this embodiment before and after passivation, and B is the corresponding band structure diagram, in which the red line represents the sample after the perovskite film is passivated, and the blue line represents the sample before the perovskite film is passivated. By comparison, it can be seen that the formation of the low-dimensional perovskite film increases the valence band top, which is more conducive to the extraction and transmission of holes.
[0046] Comparative Example 1
[0047] A large-area perovskite solar cell module, the preparation method of which is different from that of Example 1 in that the amount of benzamidine hydrochloride used in step 3) is 0, and only a mixed solvent of IPA, EA and DMF is used for treatment, and the other conditions are the same as those of Example 1.
[0048] The morphology of the perovskite film obtained in step 3) of this comparative example is as follows Figure 3 As shown in C, there are still a lot of PbI on the surface of the treated perovskite film. 2 grains, indicating that only IPA, EA and DMF mixed solvents cannot eliminate PbI on the film surface 2 grains, and there is still significant non-radiative recombination caused by defects.
[0049] The performance of the large-area perovskite solar cell modules obtained in Example 1 and Comparative Example 1 was tested. The test results were as follows: Figure 7 As shown, the conversion efficiency of the large-area perovskite solar cell module prepared in Example 1 is much higher than that in Comparative Example 1, with an efficiency of 18.30%. OC is 11.88V, J SC 1.95mA / cm 2 , the fill factor (FF) is 0.79, the conversion efficiency of the perovskite solar cell module prepared in Comparative Example 1 is only 12.72%, V OC is 11.47V, J SC 1.88mA / cm 2 , the filling factor (FF) is 0.59.
[0050] Figure 4 Comparative Example 1 is the XRD diagram of the perovskite film after treatment in step 3) of this comparative example. At this time, the perovskite film does not show the diffraction peak of the low-dimensional perovskite.
[0051] Comparative Example 2
[0052] A large-area perovskite solar cell module, the preparation method of which is different from that of Example 1 in that there is no PbI on the surface of the perovskite film 2 Grains, step 2) the concentration of FAI in the perovskite precursor solution is 1.2M, and no excessive addition of PbI 2 , PbI 2 The concentration of is 1.2M, the concentration of MACl is 0.2M, and the concentration of PbCl 2 The concentration of is 0.02M, and the other conditions are the same as those in Example 1.
[0053] like Figure 5 Shown are the XRD patterns of the perovskite film obtained in step 2) of this comparative example before and after passivation treatment, wherein the untreated sample is the perovskite film before passivation treatment, and the treated sample is the perovskite film after passivation treatment. It can be seen that no diffraction peak of low-dimensional perovskite appears before and after passivation treatment, indicating that for a perovskite film not containing lead iodide grains, even if the passivation treatment is performed using the method of Example 1, low-dimensional perovskite cannot be formed, and the (100) plane strength of the perovskite film itself becomes lower after passivation treatment, resulting in poor film performance.
[0054] Comparative Example 3
[0055] A large-area perovskite solar cell module, the preparation method of which is different from that of Example 1 in that in step 3), the solvent for dissolving benzamidine hydrochloride is only IPA of the same volume as the mixed solvent of Example 1, rather than a mixed solvent of IPA, EA and DMF. At this time, benzamidine hydrochloride is completely dissolved in IPA, and the other conditions are the same as those of Example 1.
[0056] The morphology of the perovskite film obtained in step 3) of this comparative example is as follows Figure 3 As shown in D, it can be seen that there are still a lot of PbI on the surface of the film after passivation treatment. 2 grains, indicating that this passivation method cannot completely eliminate PbI 2 , and thus cannot play an effective passivation role and cannot achieve good encapsulation of perovskite solar cell modules. This is because IPA cannot interact strongly with lead iodide and cannot make lead iodide fully react with benzamidine hydrochloric acid, resulting in a large amount of lead iodide remaining and non-radiative recombination not being significantly eliminated.
[0057] Figure 4 Comparative Example 3 is the XRD pattern of the perovskite film after treatment in step 3) of this comparative example. At this time, the perovskite film shows the diffraction peak of lead iodide and a very weak diffraction peak of low-dimensional perovskite.
[0058] Figure 8 V of the perovskite solar cells prepared in Example 1, Comparative Example 1 and Comparative Example 3 OCThe graph of changes with light intensity. Change the light intensity and test the corresponding V OC , and a linear fit was performed on the data. The obtained linear graph is shown in Figure 8 The slope reflects the non-radiative recombination caused by defects. The smaller the slope, the weaker the non-radiative recombination caused by defects. Figure 8 It can be seen that the perovskite film corresponding to Example 1 has the least defects.
[0059] The large-area perovskite solar cell modules prepared in Example 1, Comparative Example 1 and Comparative Example 3 were tested for long-term working stability. The temperature was room temperature and the illumination was 1 sun equivalent of LED light. The maximum power point of the perovskite solar cell module was tracked and the test results were recorded every 4 minutes. The test results are shown in FIG. Fig. 9 As shown, the perovskite solar cell module of Example 1 can still maintain 80% of the initial efficiency after 600 hours of aging, while the efficiency of the perovskite solar cell module of Comparative Example 1 is reduced to about 20% of the initial efficiency after 300 hours of aging.
Claims
1. A passivation method for a perovskite film, characterized in that: The following steps are involved: 1) Preparing a FAPbI3 perovskite film with a surface rich in lead iodide grains: coating a FAPbI3 perovskite precursor solution on a conductive substrate with an electron transport layer, and then annealing the conductive substrate to obtain a FAPbI3 perovskite film with a surface rich in lead iodide grains on the surface of the conductive substrate; 2) preparing a passivation layer: applying a benzamidine hydrochloride solution to the surface of the FAPbI3 perovskite film obtained in step 1) by a slit coating method, and then annealing, wherein the benzamidine hydrochloride reacts with the lead iodide on the surface of the FAPbI3 perovskite film to form a low-dimensional passivation layer, thereby passivating the perovskite film. The low-dimensional passivation layer in step 2) is a two-dimensional perovskite; Step 1) The preparation method of the FAPbI3 perovskite film is as follows: dissolving formamidine hydroiodide, PbI2, methylamine hydrochloride powder and lead chloride in a mixed solvent to obtain a FAPbI3 perovskite precursor solution, and the obtained FAPbI3 perovskite precursor solution is printed on the surface of a conductive substrate with an electron transport layer by a slit coating method, the slit width between the printing head and the conductive substrate is 100-150 μm, the moving speed of the printing head is 4-7 mm / s, the liquid output rate is 0.6-1.5 mL / min, the air pressure of the air knife is 0.3-0.6 MPa, and then annealing at 120-150°C for 30-60 min to obtain a FAPbI3 perovskite film on the surface of the conductive substrate; Step 2) The benzamidine hydrochloride solution has a concentration of 1.0 to 6.0 mg / mL, and is obtained by dissolving benzamidine hydrochloride in a mixed solvent of isopropanol, ethyl acetate and N,N'-dimethylformamide, wherein the volume ratio of isopropanol to ethyl acetate is 9:1, and the amount of N,N'-dimethylformamide added per milliliter of the mixed solvent is 4 to 8 μL.
2. The passivation method of the perovskite film according to claim 1, characterized in that: Step 1) The conductive substrate is an FTO or ITO substrate after etching and cleaning; the electron transport layer is one of a tin oxide film, a titanium oxide film, and a zinc oxide film.
3. The passivation method of the perovskite film according to claim 1, characterized in that: Step 1) The thickness of the FAPbI3 perovskite film is 600-800 nm.
4. The passivation method of the perovskite film according to claim 1, characterized in that: The mixed solvent is obtained by mixing ethylene glycol methyl ether and dimethyl sulfoxide in a volume ratio of 9:
1.
5. The passivation method of the perovskite film according to claim 1, characterized in that: The process conditions of the slit coating method in step 2) are: the gap width between the printing head and the conductive substrate is 80-120 μm, the moving speed of the printing head is 5-10 mm / s, and the liquid discharge rate is 0.3-0.6 mL / min.
6. A perovskite film prepared by the passivation method according to any one of claims 1 to 5.
7. The perovskite solar cell prepared by the perovskite thin film according to claim 6, characterized in that: The specific preparation method is: depositing a hole transport layer on the surface of the perovskite film, and then depositing an electrode on the surface of the hole transport layer, so as to obtain a perovskite solar cell.
8. The large-area perovskite solar cell module prepared by the perovskite thin film according to claim 6, characterized in that: The specific preparation method is as follows: a hole transport layer is deposited on the surface of the perovskite film, and then divided into multiple areas by laser scribing, and then an electrode is deposited on the surface of the hole transport layer, and laser scribing is performed again to obtain a large-area perovskite solar cell module.
Citation Information
Patent Citations
Method for preparing large-area and high-quality perovskite thin film by using green solvent
CN116437778A